2009
DOI: 10.2207/qjjws.27.22s
|View full text |Cite
|
Sign up to set email alerts
|

Melting Phenomenon during Ultra-High-Speed GTA Welding Method using Pulse-heated Hot-wire

Abstract: The purpose of this study is to develop the ultra-high-speed GTA welding process with hot-wire system using pulsed current to heat filler wire. For precise control of the ultra-high-speed (over 5 m/min) GTA welding, it is necessary to understand deeply the ultra-high-speed welding phenomenon. The melting phenomenon of filler wire was observed in detail by a high-speed camera and filler wire temperature was measured precisely by a radiation thermometer. As a result, precise temperature distribution of filler wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 2 publications
(1 reference statement)
0
10
0
4
Order By: Relevance
“…Considering further dilution ratios -found raised for pulsed current GTAW -and correspondingly the constant ratio between wire feed rate and hot-wire current one may suggest though the results from Shinozaki et al [14] as approved; supposing that filler wire melting is mainly influenced by the hot-wire current instead of being a function of the arc current. However, we suggest that further work appears required in this conjunction to assess both these assumptions as well as evaluating the relationship between wire feed rate, hot-wire current and arc current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering further dilution ratios -found raised for pulsed current GTAW -and correspondingly the constant ratio between wire feed rate and hot-wire current one may suggest though the results from Shinozaki et al [14] as approved; supposing that filler wire melting is mainly influenced by the hot-wire current instead of being a function of the arc current. However, we suggest that further work appears required in this conjunction to assess both these assumptions as well as evaluating the relationship between wire feed rate, hot-wire current and arc current.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve high weld travel speed and acceptable quality it was found that the wire pre-heating temperature is the most important parameter. Directly related to [13], Shinozaki et al [14] have thoroughly studied phenomena caused by either the wire temperature and arc thermal input. The authors concluded that filler wire melting is mainly affected by wire pre-heating temperature and parent material melting is mainly caused by the welding arc.…”
Section: Advanced Gas Tungsten Arc Weld Surfacing Current Status and mentioning
confidence: 99%
“…Como solução a esse problema, fontes de corrente alternada são usadas, dessa forma a alternância entre a polaridade negativa e positiva a uma determinada frequência, diminuem consideravelmente o sopro magnético [6]. No trabalho de Shinozaki et al [7] destaca-se outro sistema de aquecimento do arame, que também trabalha com o princípio de efeito Joule, mas nesse caso utilizaram corrente pulsada em uma determinada frequência e polaridade, com o objetivo de eliminar alguns problemas, principalmente o sopro magnético do arco. Segundo a informação disponibilizada pelo CCWJ [8], eles também utilizam uma corrente pulsada para aquecer o arame, porém, é possível notar que a corrente usada durante o período de base é bastante baixa, devido ao menor sopro magnético sobre o arco voltaico.…”
Section: Estudo Do Processo Tig Hot-wire Com Materials De Adição Aisi-unclassified
“…Este defeito é formado por distúrbios magnéticos (campos) perto do arco voltaico, que provocam o desvio e diminuição no controle do jato de plasma [11][12][13]. Como foi mencionado anteriormente, o processo TIG Hot-Wire na sua forma mais simples, com corrente contínua constante, produz um sopro magnético sobre o arco voltaico [5][6][7]9]. Porém, no trabalho realizado por Burt [14] foi utilizado um sistema de aquecimento do arame com corrente alternada de baixa frequência com o propósito de provocar uma pequena oscilação no arco voltaico mediante o sopro magnético, conseguindo diluições inferiores ao 8% com uma taxa de deposição de 6,43 kg/h, demonstrando assim que o sopro magnético pode ser benéfico, em certas condições.…”
Section: Estudo Do Processo Tig Hot-wire Com Materials De Adição Aisi-unclassified
See 1 more Smart Citation